Polymer/POSS Nanocomposites and Hybrid Materials Preparation, Properties, Applications (Springer Series on Polymer and Composite Materials,, 2018)
This book provides an overview of polymer nanocomposites and hybrid materials with polyhedral oligomeric silsesquioxanes (POSS). Among inorganic nanoparticles, functionalized POSS are unique nano-building blocks that can be used to create a wide variety of hybrid and composite materials, where precise control of nanostructures and properties is required. This book describes the influence of incorporation of POSS moieties into (organic) polymer matrices on the mechanical, thermal and flammability behavior of composites and hybrid organic-inorganic materials. Importantly, POSS-containing materials can be bio-functionalized by linking e.g. peptides and growth factors through appropriate surface modification in order to enhance the haemo-compatibility of cardiovascular devices made of these materials. This volume includes descriptions of synthesis routes of POSS and POSS-containing polymeric materials (e.g. based on polyolefines, epoxy resins and polyurethanes), presentation of POSS' role as flame retardants and as biocompatible linker, as well as the depiction of decomposition and ageing processes.